Poverty and inequality in South Africa: critical reflections. Issue 6 (2nd November 2019) - Francis, David; Webster, Edward
ABSTRACT: South Africa is a paradox; on the one hand, it is one of the most unequal countries in the world. Half of all South Africans continue to live in poverty, economic growth has stagnated and inflation remains high, while the unemployment rate continues to climb towards 30%. On the other hand, it has one of the most progressive constitutions in the world, with a bill of rights that foregrounds expanded socioeconomic rights. We provide an overview of the latest statistics on poverty and inequality in light of overarching economic policies, and the socioeconomic guarantees of the Constitution. We argue that South Africa's inability to meaningfully address the high levels of inequality is due to insufficient attention to the way power reproduces inequality. We present a definition of power that includes social and market power, and emphasise the importance of a theory of power in understanding the reproduction of inequality.